Antifungal Therapy for Complicated Intra-Abdominal Infection: A Case Report - Mega Halida; Vera Irawany; Adhrie Sugiarto (Jurnal Sehat Indonesia (JUSINDO), 2026)
Complicated intra-abdominal infection (cIAI) is a serious condition characterized by the extension of infection beyond the gastrointestinal tract into the peritoneal cavity and is associated with high morbidity and mortality. Management of cIAI requires a comprehensive approach, including prompt diagnosis, adequate source control, and appropriate antimicrobial therapy. This case report describes the role of antifungal therapy in the management of cIAI in a critically ill patient with multiple risk factors for invasive fungal infection. A 52-year-old woman with a history of cervical cancer treated with radiotherapy and chronic hemodialysis presented with abdominal pain, nausea, vomiting, and inability to tolerate oral intake. Diagnostic evaluation revealed obstructive ileus and necrotic ileal tissue requiring exploratory laparotomy and intestinal resection. Postoperatively, the patient was admitted to the intensive care unit and received broad-spectrum antibiotics combined with fluconazole as empirical antifungal therapy. Clinical and laboratory improvements were observed during intensive care management, leading to stabilization and subsequent transfer to a high-dependency unit. This case highlights the importance of considering antifungal therapy in healthcare-associated intra-abdominal infections, particularly among immunocompromised and critically ill patients at risk of Candida infection. Early recognition, adequate source control, and individualized antimicrobial selection remain essential for optimizing patient outcomes.